2021
DOI: 10.1155/2021/5514708
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary Game of Trust in Public-Private Partnership Project Networks

Abstract: In public-private partnership (PPP) projects, the government plays a role as both regulator and participant. Trust between the government and the private sector is important as it may affect project performance and even cause the problem of a breach of contract, which may lead to project failure. Little is known, however, about the formation and evolution mechanisms of trust in this context. This study analyses the complex evolution of trust in PPP project networks. An evolutionary game of trust model between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…The primary reason behind this is the inconsistent cooperation status between the investment company and the supplier, with the investment company often occupying a dominant position while the supplier remains in a passive state. Previous research has also indicated that the market institutional environment and imbalanced power distribution indirectly decrease the level of trust between partners, thereby impeding the smooth implementation of projects [45,51]. Therefore, it is crucial for the government to strengthen the supervision of moral hazard behaviors exhibited by investment companies, penalize opportunistic behaviors, reduce the status inequality between investment companies and suppliers, enhance incentives for active cooperation, improve the reward and punishment mechanism, and foster a conducive market environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary reason behind this is the inconsistent cooperation status between the investment company and the supplier, with the investment company often occupying a dominant position while the supplier remains in a passive state. Previous research has also indicated that the market institutional environment and imbalanced power distribution indirectly decrease the level of trust between partners, thereby impeding the smooth implementation of projects [45,51]. Therefore, it is crucial for the government to strengthen the supervision of moral hazard behaviors exhibited by investment companies, penalize opportunistic behaviors, reduce the status inequality between investment companies and suppliers, enhance incentives for active cooperation, improve the reward and punishment mechanism, and foster a conducive market environment.…”
Section: Discussionmentioning
confidence: 99%
“…(5) The hypothesis of trust between game agents. It is assumed that the trust among game players exists objectively, that the trust level α i is measurable, and that the trust level changes with the deepening of the communication and cooperation of game players [45]. In the process of cooperation between investment companies and suppliers, the trust between investment companies and suppliers can promote the harmonious cooperation process.…”
Section: Problem Description and Basic Assumptionsmentioning
confidence: 99%
“…For example, Carbonara and Pellegrino established an approach to enumerate the ideal highest and lowest figures for income in a situation whereby there is fair allocation of risk and rewards between public and private institutions. In addition, frameworks and models that seek to optimize risk-sharing in PPPs enhance the efficiency of PPPs and promote synergy between the stakeholders involved [7,8].…”
Section: The Nature Of Pppsmentioning
confidence: 99%